Gout is associated with more comorbidities, poorer health-related quality of life and higher healthcare utilisation in US veterans. Issue 9 (4th January 2008) - Singh, J A; Strand, V
Abstract : Objective: To better understand the impact of gout on functional status, health-related quality of life (HRQoL), mortality and healthcare utilisation in US veterans. Methods: All veterans seen in Veterans Integrated Service Network-13 from 1 October 1996 to 31 March 1998 received mailed surveys asking about demographic characteristics; performance of activities of daily living and HRQoL by Short Form-36 (SF-36) for Veterans. Administrative data included demographics; inpatient/outpatient healthcare utilisation; ICD-9 codes for gout, medical comorbidities and arthritis excluding gout—"arthritic comorbidity" and 1-year mortality. Multivariable estimates compared results between veterans with/without gout using least means squared. Results: Subjects with gout were significantly older, retired, not married, current non-smokers, with more comorbidities. Multivariable-adjusted bodily pain was somewhat worse (49.7 vs 47.1, p<0.01) and mental health (66.7 vs 68.6, p<0.01) domain scores somewhat better in patients with gout, both differences significant but not clinically meaningful (less than threshold of 5–10 points); other SF-36 domain and summary scores and functional limitations were similar. Medical or arthritic comorbidities predicted clinically/statistically lower adjusted scores in all SF-36 domains and physical domains (physical component summary), respectively. Patients with gout had significantly more annual primary care visits (3.5 vs 2.7, p<0.001) and admissions to hospital (18.3% vs 15.1%, p<0.01), fewer mental health visits (10.1% vs 13.7%, p<0.01) and similar mortality (2.6% vs 2.2%, p = 0.23). Conclusions: Gout is independently associated with higher medical and arthritic comorbidity, primary care and inpatient utilisation. Poorer HRQoL, functional limitation and higher mortality noted in univariate analyses in patients with gout were attributable to higher comorbidity and sociodemographic characteristics.